2020
DOI: 10.1016/j.jpeds.2020.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Oral Paracetamol vs Oral Ibuprofen in Patent Ductus Arteriosus: A Randomized, Controlled, Noninferiority Trial

Abstract: Objective To test the hypothesis that oral paracetamol is non-inferior to oral ibuprofen in closing hemodynamically significant patent ductus arteriosus (hsPDA) with an a priori noninferiority (NI) margin of 15%. Study design Multicenter, randomized, controlled, NI trial conducted in level III neonatal intensive care units. Consecutively inborn preterm neonates of <32 weeks of gestation with hsPDA were included. Those with structural heart disease, major malformations, and contraindications for enteral feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
1
20
1
4
Order By: Relevance
“…We report a lower probability of successful PDA closure (42.4%) following acetaminophen compared to the previous published RCTs, which range from 70 to 100% successful PDA closure [ 4 , 6 12 , 14 ]. This is likely related to differences in the patient population of the enrolled subject as well as our unit’s clinical practice of symptomatic PDA treatment strategy used to treat hs-PDA, which were potentially causing pulmonary comorbidity of continued need for mechanical ventilation and inability to wean.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…We report a lower probability of successful PDA closure (42.4%) following acetaminophen compared to the previous published RCTs, which range from 70 to 100% successful PDA closure [ 4 , 6 12 , 14 ]. This is likely related to differences in the patient population of the enrolled subject as well as our unit’s clinical practice of symptomatic PDA treatment strategy used to treat hs-PDA, which were potentially causing pulmonary comorbidity of continued need for mechanical ventilation and inability to wean.…”
Section: Discussioncontrasting
confidence: 51%
“…Acetaminophen is increasingly being used for initial medical management of PDA as demonstrated by multiple case series [ 23 , 27 , 28 ] and recent randomized controlled trials [ 4 , 6 10 , 12 , 14 ]. In our study, with symptomatic PDA treatment strategy, we found that infants >26 weeks GA or with PDA size ≤0.2 cm were nearly twice as likely to have successful PDA closure after acetaminophen compared to infants ≤26 weeks or with PDA size >0.2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paired comparisons between AA, indomethacin and ibuprofen revealed no difference in PDA closure rates (Table 1A; many oral drug trials not shown). A recent non‐inferiority trial in which oral AA and ibuprofen were compared confirmed the result 18 . In placebo‐controlled trials, NSAIDs increased the PDA closure and AA showed a similar trend (Table 1B).…”
Section: Review Of Trials Of Medical Closure Of Pdasupporting
confidence: 52%
“…Of published clinical trials, only study of Kumar et al ( 31 , 42 ) has a non-inferiority design but administration of treatment was oral and patients included were <32 weeks of gestation. One of the main inconveniences of this design is the large population size needed to demonstrate non-inferiority.…”
Section: Discussionmentioning
confidence: 99%